2020
DOI: 10.1039/c9py01557d
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional adenine-functionalized supramolecular micelles for highly selective and effective cancer chemotherapy

Abstract: Adenine-functionalized supramolecular micelles are rapidly endocytosed by cancer cells and enable selective induction of tumor cell death, without harming normal cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 44 publications
1
16
0
Order By: Relevance
“…A new low-molecular-weight supramolecular polymer micelle, adenine end-capped difunctional oligomeric A-PPG, was successfully prepared using our previously described simple, one-step synthesis [ 45 , 46 , 48 ]. To achieve a photodynamic chemotherapeutic effect, we selected 5-ALA as a photosensitizer moiety to enhance release of the chemotherapy drug DOX from the micelles at tumor sites, as presented in Scheme 1 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A new low-molecular-weight supramolecular polymer micelle, adenine end-capped difunctional oligomeric A-PPG, was successfully prepared using our previously described simple, one-step synthesis [ 45 , 46 , 48 ]. To achieve a photodynamic chemotherapeutic effect, we selected 5-ALA as a photosensitizer moiety to enhance release of the chemotherapy drug DOX from the micelles at tumor sites, as presented in Scheme 1 .…”
Section: Resultsmentioning
confidence: 99%
“…In our previous study, we observed low cumulative drug release (less than 28% after 96 h) from drug-loaded A-PPG micelles under physiological conditions [ 46 ]. Thus, we investigated the ability of light irradiation to induce release of DOX from DOX/5-ALA-loaded A-PPG micelles in PBS to further explore the release behavior of the system in vitro.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Conjugation of polymers with targeting agents such as aptamers, antibody, folic acid, and proteins improve the tumor target ability in co-therapy [81,82]. Aptamers produced from nucleic acids, RNA, or DNA specifically bind to a ligand, like a cancer antigen, for targeting cancer cells [83].…”
Section: Drug Deliverymentioning
confidence: 99%